EFEKTIVITAS TERAPI RELAKSASI TERHADAP PENURUNAN STRES KERJA PADA GURU DI SMK MUHAMMADIYAH 1 PANDAA - Farida, Nurul; Ansyah, Eko Hardi (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2023)
Often, a teacher experiences work stress caused by the presence of demands and heavy workloads, but environmental conditions are less supportive. This research was conducted with the aim of determining the effectiveness of stress management using relaxation techniques in reducing the work stress experienced by teachers. In addition, this psychoeducational program gives teachers new skills, such as stress management techniques. This stress management can be done independently or in groups in everyday life. Previous research has always combined this relaxation therapy with other techniques. However, this time, the researchers wanted to know if relaxation therapy was effective if it was not combined with other techniques. The method used in this study is quantitative with a one-group pretest-posttest design. The research also uses interviews and observations as a networking technique for early informant data. The sample in this study was a permanent teacher at SMK Muhammadiyah 1 Pandaan of 35 people. Data analysis using the paired sampled t-test The results of the data analysis showed that p = 0.010   0.05, meaning there was a decrease in work stress before and after psychoeducation. These results show that stress management psychoeducation using relaxation techniques is considered effective in reducing work stress in teachers.